A hybrid hydrogel with in situ formed Ag-nanoparticles within 3D networks that exhibits broad antibacterial activities. (24th April 2020) - Wei, Chuan-Wan; Gong, Xiao-Qing; Wang, Xiao-Juan; Yang, Xin-Zhi; Gao, Shu-Qin; Lin, Ying-Wu
Abstract : A new hybrid hydrogel was constructed by in situ forming Ag NPs within the 3D network of a hydrogel that exhibits both excellent injectability and broad antibacterial activities, which makes it a potential candidate for various biomedical applications. Abstract : A new hybrid hydrogel was constructed by in situ forming silver nanoparticles (Ag NPs) within the 3D network of a hydrogel based on a tryptophan derivative containing a phenylcarbinol side group (HAIP), which was triggered by natural light, without the need of UV-irradiation or the addition of capping reagents. Remarkably, in addition to excellent thixotropy and injectability, the hybrid Ag NPs–HAIP hydrogel exhibits broad antibacterial activities without cell cytotoxicity, which makes it a potential candidate for various biomedical applications.